2000
DOI: 10.1037/0022-006x.68.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for a cost-offset model of psychotherapy allocation using generalized anxiety disorder as an example.

Abstract: As inexpensive interventions gain empirical support, there is an increasing risk that such data may be used by health maintenance organizations to unfairly restrict the number and type of therapy sessions reimbursed for all clients, even those less likely to benefit from economical treatments. As a result, it is important to identify clients who may not respond to specific therapies and to empirically support ways to treat them. Successful treatment of nonresponders is also valuable because predictors of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 63 publications
(76 reference statements)
3
120
0
3
Order By: Relevance
“…Not all patients need the same type and intensity of intervention, and for some, self-help interventions (with the support of a trained paraprofessional) may be sufficiently successful in reducing anxiety. When self-help proves to be insufficiently effective for a particular patient, a more intensive treatment can be offered, such as a standardized individual treatment by a highly trained professional therapist [35,36]. Although guided self-help interventions undoubtedly are not successful for every patient, the available research findings suggest that there are many patients for whom self-help interventions are sufficient to treat their problems successfully.…”
Section: Advantages Of Self-help Interventionsmentioning
confidence: 99%
“…Not all patients need the same type and intensity of intervention, and for some, self-help interventions (with the support of a trained paraprofessional) may be sufficiently successful in reducing anxiety. When self-help proves to be insufficiently effective for a particular patient, a more intensive treatment can be offered, such as a standardized individual treatment by a highly trained professional therapist [35,36]. Although guided self-help interventions undoubtedly are not successful for every patient, the available research findings suggest that there are many patients for whom self-help interventions are sufficient to treat their problems successfully.…”
Section: Advantages Of Self-help Interventionsmentioning
confidence: 99%
“…Newman [36] assessed its psychometric properties on the basis of studies conducted using this questionnaire. They concluded that a score of 7.5 was the optimal balance between sensitivity and specificity.…”
Section: Diagnostic and Screening Measuresmentioning
confidence: 99%
“…effective adjuncts to more conventional treatment for a variety of anxiety disorders, including panic disorder, agoraphobia, social phobia, obsessive-compulsive disorder, and generalized anxiety disorder (Newman, 2000). With the advent of powerful, inexpensive hand-held computers, it has become possible to provide a realistic version of CBT that may be used in the patient's own environment Preliminary studies by Kenardy, Fried, Taylor, and Kraemer (1992) on the use of hand held computers to aid monitoring of anxiety and coping ability among panic disorder patients showed that the computers were well accepted, led to increased compliance and more reliable self-monitoring.…”
mentioning
confidence: 99%